FRI0628-HPR Advanced Practice Musculoskeletal Physiotherapists in Rheumatology- A National Report of The 2014 Data. (15th July 2016) - Ashton, J.; Breen, R.; Brennan, A.; Callanan, E.; Farrell, C.; Moore, D.; Kenny, P.; Carey, D.; Fitzgerald, O.
Abstract : Background: Research studies have supported the role of Advanced Practice Physiotherapists (APP's) acting as first contact practitioners in the management of musculoskeletal (MSK) patients 1 . In 2012, funding was approved for 24 APP posts in Ireland through the Clinical Strategy and Care Programmes Directorate of the Health Service Executive (HSE) in Ireland. These posts were to provide orthopaedic and rheumatology triage clinics across 16 hospitals throughout the country as a waiting list initative for patients with MSK complaints. Objectives: i)To present the data reported on the throughput of Rheumatology patients seen by the APPs nationally in 2014. Methods: 13 sites provided MSK triage through rheumatology clinics nationally in 2014. While each post has a target of seeing 1, 000 patients per year it has been reported that APP's see a ratio of 5:1 orthopaedic to rheumatology patients. Data was collected monthly from all sites and reported directly to the rheumatology clinical care programme. Descriptive data was analysed using a Microsoft® Excel package. Results: 2, 177 new and 530 return rheumatology patients were seen nationally in 2014. Regarding new patients the most common areas were shoulder (n=329, 15.1%) and lumbar spine (n=288, 13.2%), 35.2% (n=766) had multiple pain sites. Regarding waiting times 58.6% (n=1275) were seen within 6months of referral and 21% (n=457) had imaging ordered. 40.1% (n=873) were referred for physiotherapy within the hospital or primary care. 63.3% (n=1378) were discharged directly from the APP clinic and 15% (n=327) were referred on to another medical speciality. Conclusions: APPs have been effective in triaging MSK referrals within a rheumatology setting. A large proportion of patients were discharged back to the referring source. References: Desmeules et al (2012) Advanced practice physiotherapy in patients with musculoskeletal disorders: a systematic review. BMC Musculoskeletal Disorders. 13: 107–128. Acknowledgement: The authors would like to acknowledge the work of the APP's nationally in the collection of the data. Disclosure of Interest: None declared